Pipistrellus (Pipistrellus) kuhlii subsp. kuhlii Kuhl 1817 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pipistrellus (Pipistrellus) kuhlii subsp. kuhlii Kuhl 1817 Pipistrellus (Pipistrellus) kuhlii subsp. kuhlii Kuhl 1817, Die Deutschen Fledermause. Hanau: 14. Type Locality: Italy, Friuli-Venezia Giulia, Trieste. Synonyms: Pipistrellus (Pipistrellus) kuhlii subsp. albicans Monticelli 1886; Pipistrellus (Pipistrellus) kuhlii subsp. albolimbatus Küster 1835; Pipistrellus (Pipistrellus) kuhlii subsp. alcythoe Bonaparte 1837; Pipistrellus (Pipistrellus) kuhlii subsp. marginatus Cretzschmar 1830; Pipistrellus (Pipistrellus) kuhlii subsp. marginatus Bonaparte 1841; Pipistrellus (Pipistrellus) kuhlii subsp. minuta Loche 1867; Pipistrellus (Pipistrellus) kuhlii subsp. pallidus Heim de Balsac 1936; Pipistrellus (Pipistrellus) kuhlii subsp. pullatus Monticelli 1886; Pipistrellus (Pipistrellus) kuhlii subsp. saharae Heim de Balsac 1936; Pipistrellus (Pipistrellus) kuhlii subsp. ursula Wagner 1840. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 476, DOI: 10.5281/zenodo.7316519